2014
DOI: 10.1111/dgd.12111
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease‐mediated genome editing: At the front‐line of functional genomics technology

Abstract: Genome editing with engineered endonucleases is rapidly becoming a staple method in developmental biology studies. Engineered nucleases permit random or designed genomic modification at precise loci through the stimulation of endogenous double-strand break repair. Homology-directed repair following targeted DNA damage is mediated by co-introduction of a custom repair template, allowing the derivation of knock-out and knock-in alleles in animal models previously refractory to classic gene targeting procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 149 publications
0
38
0
1
Order By: Relevance
“…This relationship between amino acid sequence and DNA recognition enabled the engineering of specific DNA-binding domains. DNA binding domain is fused with the FokI nuclease enzyme which confers extreme site specificity and has expanded the possibility of specific editing in a number of genomes (38,39).…”
Section: Major Genome Editing Toolsmentioning
confidence: 99%
“…This relationship between amino acid sequence and DNA recognition enabled the engineering of specific DNA-binding domains. DNA binding domain is fused with the FokI nuclease enzyme which confers extreme site specificity and has expanded the possibility of specific editing in a number of genomes (38,39).…”
Section: Major Genome Editing Toolsmentioning
confidence: 99%
“…Further improvement was achieved using tol2 or piggyBac transposons (Macdonald et al, 2012;Park and Han, 2012;Glover et al, 2013), and the expression of the introduced GFP gene was observed consistently without transgene silencing. More sophisticated genome editing could be achieved by recently developed approaches using zinc-finger nuclease (ZFN), transcription activator-like effector nuclease (TALEN), or clustered regularly interspaced short palindromic repeats (CRISPR/Cas) (see review: Sakuma and Woltjen, 2014).…”
Section: Gene Transfermentioning
confidence: 99%
“…Genome editing technology relies on endogenous repair pathways of DNA double-strand break (DSB), triggered by site-specific nucleases such as zinc-finger nucleases (ZFNs), transcription activator-like effector nucleases (TALENs), and clustered regularly interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (Cas9) (Sakuma and Woltjen 2014). The primary concept of genome editing based on non-homologous end-joining (NHEJ)-dependent gene knockout and homologous recombination (HR)-mediated gene knock-in.…”
Section: Introductionmentioning
confidence: 99%